Opportunistic Use of Chest X-Ray for Identifying Older Adults at risk of Osteoporosis and not Meeting Criteria for Screening - Naga Ramesh Chinapuvvula; Marsha Hatley; Raia Khan; Muhammad Awiwi; Jude des Bordes; Nahid Rianon (Journal of Primary Care & Community Health, 2025)
Introduction: Screening for osteoporosis is mainly done by measuring bone mineral density using dual-energy X-ray absorptiometry (DXA) scan. Screening does not usually start until 65 years. Many people 50 to 65 years may unknowingly suffer from progressive bone loss and may be at risk of osteoporosis. Opportunistic use of chest X-rays obtained for other indications could potentially be used to identify patients with signs of bone demineralization and at risk of osteoporosis in primary care settings particularly where DXA may not be readily available. We aimed at comparing the prevalence of bone demineralization using chest radiographs obtained for any indication in patients 50 to 65 years seen at an emergency department, as assessed from their radiology reports and by independent review by a radiologist. We also sought to explore clinical and demographic associates of low bone mass (LBM) among this population. Methods: We conducted a cross-sectional review of electronic medical records of patients 50 to 65 years, who had obtained a chest X-ray at the emergency department of a large Level 1 trauma center in an urban teaching hospital between May 1, 2021, and May 31, 2021. We estimated the prevalence of “bone demineralization” from the X-rays reports and compared it with that obtained by an independent radiologist’s review. We also used the 2020 US population census figures to estimate the number of people 50 to 65 years potentially at risk of LBM and investigated demographic and clinical correlates of LBM. Results: We reviewed 390 patient records, comprising 201 (51.5%) males and 189 (48.5%) females. Bone demineralization comment was found in 4 (1.0%) reports while radiologist review found 49 (12.6%). Applying sex-adjusted prevalence of 13.1% (using the direct method, with the 2020 US population as standard) to the 64.1 million adults 50 to 64 years in the US population, we estimated that approximately 8.4 million people will have bone demineralization in the population group. LBM was associated with hypertension in women (OR = 2.41, 95% CI = 1.03-5.64). Conclusion: Use of opportunistic chest X-rays may be feasible in identifying patients at risk of bone loss outside the traditional screening age particularly in areas where DXA may not be readily available.